Analisis Implikatur dalam Kolom Komentar Akun TikTok @Owner Daviena Skincare sebagai Representasi Komunikasi Digital Masyarakat (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to identify the forms of implicature and language styles employed by netizens when commenting on the TikTok account @owner daviena skincare. Using a qualitative descriptive method with a pragmatic approach, this research explores the linguistic phenomena occurring in the comment section of selected posts. Data collection techniques include non-participant observation, attentive listening, note-taking, and documentation. The theoretical framework is based on the concept of implicature, which covers both conventional and non-conventional implicatures. The findings reveal that the comment section displays a variety of implicatures, with the dominant purposes being to offer advice, deliver criticism, and express support toward the content creator. Conventional implicatures appear when the meaning conveyed is closely tied to specific linguistic expressions, while non-conventional implicatures are identified in cases where the intended meaning relies on contextual interpretation. In terms of language style, the majority of comments utilize informal and conversational expressions, characterized by colloquial vocabulary, slang, and abbreviations that are common in online interactions. The analysis also highlights that the interplay between implicature and informal language style reflects the spontaneous and dynamic nature of digital communication on social media. Such interactions not only serve as a platform for engagement but also illustrate how language is adapted to suit the immediacy and brevity of online discourse. The study concludes that understanding implicature in social media contexts is essential for interpreting the underlying meanings beyond the literal content of user comments. Furthermore, the predominance of informal styles demonstrates the influence of digital culture on contemporary language use, particularly among netizens engaged in beauty and skincare communities.